2021
DOI: 10.3390/jcm10214963
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Implants in the Aesthetic Zone: Is Socket Shield Technique a Predictable Treatment Option? A Narrative Review

Abstract: (1) Background. Dental implant placement in the anterior region requires extreme precision due to relatively high aesthetic demand. This narrative review aimed to analyse some of the available clinical studies of the socket-shield technique and determine its viability for dental implant survival/success and complication rates. (2) Methods. An electronic search for publications was performed using the Cochrane, PubMed-MEDLINE, Web of Science, and Google Scholar databases. All electronic searches included human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…3,4 This creates an unfavorable labio-palatal discrepancy and produces the "fixture-socket gap" around the coronal portion of the implant, known as the labial gap especially in sockets with thin bone. 5,6 Although this gap has the potential to repair spontaneously in some cases, 2 still previous studies reported that this gap cannot be completely filled without using a regenerative material. [7][8][9] It has been claimed that buccal/labial gap augmentation contributes to the final esthetic success of the dental implant, where the regenerative material acts as a scaffold to maintain the blood clot, promote bone formation, compensate for the postextraction socket remodeling and maintain the buccal bone thickness and thereby preventing the buccal contour collapse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 This creates an unfavorable labio-palatal discrepancy and produces the "fixture-socket gap" around the coronal portion of the implant, known as the labial gap especially in sockets with thin bone. 5,6 Although this gap has the potential to repair spontaneously in some cases, 2 still previous studies reported that this gap cannot be completely filled without using a regenerative material. [7][8][9] It has been claimed that buccal/labial gap augmentation contributes to the final esthetic success of the dental implant, where the regenerative material acts as a scaffold to maintain the blood clot, promote bone formation, compensate for the postextraction socket remodeling and maintain the buccal bone thickness and thereby preventing the buccal contour collapse.…”
Section: Introductionmentioning
confidence: 99%
“…It is well‐established that the dimensional changes and remodeling of the alveolar ridge represent a physiologic sequela of tooth extraction and is inevitable especially the labial bone wall 3,4 . This creates an unfavorable labio‐palatal discrepancy and produces the “fixture‐socket gap” around the coronal portion of the implant, known as the labial gap especially in sockets with thin bone 5,6 . Although this gap has the potential to repair spontaneously in some cases, 2 still previous studies reported that this gap cannot be completely filled without using a regenerative material 7–9 …”
Section: Introductionmentioning
confidence: 99%
“…Known for their length and greater strength than other types of teeth, canines are typically securely held in the dental arch and are less affected by external forces. The protrusion of the canine's tooth body outward helps create a self-cleaning mechanism, reducing the likelihood of tooth decay or damage, as discussed in many previous studies [1,19,20].…”
Section: A Clinical Condition and Medical History Of The Patientsmentioning
confidence: 92%
“…In the realm of oral health, teeth play a pivotal role in performing essential functions such as mastication, pronunciation, facial morphology, and expressing the emotional and personal traits of each individual, particularly contributing to the esthetic appeal of one's smile [1]. According to the nationwide oral health survey conducted by Tuong and Hai [2], the prevalence of tooth loss among the population is 41.6%.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent bone resorption following the extraction, one method is the immediate placement of the dental implant into the fresh extraction socket [ 6 , 7 , 8 ]. The rationale behind this is a close adaptation of the dental implant to the socket wall can reduce bone resorption [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%